STATUS KEPEMILIKAN TANAMAN YANG BERADA DI ATAS HAK ATAS TANAH MILIK ORANG LAIN - Abd Hamid Bakir; Abraham Ferry Rosando (Gapenas Publisher, 2023)
The principle of horizontal separation regulates the principle that separates land from the objects/buildings above it, meaning that the land owner does not automatically have the right to the objects/buildings above it, so whoever builds or builds them will own them. non-owner rights. The research used in this paper is using normative legal research, where normative legal research must be stated in a paper, it is sufficient to state that this research is legal research and an approach to legislation (Statute Approach). In this study, to find out the status of plants that are on other people's land, which is on the principle of horizontal separation of buildings, and plants that are on the ground are not part of the land. Land rights do not automatically include ownership of buildings and plants on it. In civil law there are 2 legal remedies: Ordinary legal remedies are appeal, cassation, and verzet in article 180 HIR. and Extraordinary legal remedies are resistance to third parties and under review (civil request).